2021
DOI: 10.1093/jmicro/dfab028
|View full text |Cite
|
Sign up to set email alerts
|

Miniature microscopes for manipulating and recording in vivo brain activity

Abstract: Here we describe the development and application of miniature integrated microscopes (miniscopes) paired with microendoscopes that allow for the visualization and manipulation of neural circuits in superficial and subcortical brain regions in freely behaving animals. Over the past decade the miniscope platform has expanded to include simultaneous optogenetic capabilities, electrically-tunable lenses that enable multi-plane imaging, color-corrected optics, and an integrated data acquisition platform that stream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 142 publications
0
15
0
Order By: Relevance
“…Currently, there are two main segmentation programs used for microendoscope data: PCA-ICA and constrained nonnegative matrix factorization for microendoscope imaging (CNMFe). Although CNMFe reduces the contribution of fluorescent signal from cells above and below the imaging plane when compared to PCA-ICA, it also has lower precision and identifies false positive cells ( 55 ). In our hands, we found CNMFe had poor recognition for the somatic compartment of cells and therefore opted to use PCA-ICA data for analysis of calcium traces.…”
Section: Methodsmentioning
confidence: 99%
“…Currently, there are two main segmentation programs used for microendoscope data: PCA-ICA and constrained nonnegative matrix factorization for microendoscope imaging (CNMFe). Although CNMFe reduces the contribution of fluorescent signal from cells above and below the imaging plane when compared to PCA-ICA, it also has lower precision and identifies false positive cells ( 55 ). In our hands, we found CNMFe had poor recognition for the somatic compartment of cells and therefore opted to use PCA-ICA data for analysis of calcium traces.…”
Section: Methodsmentioning
confidence: 99%
“…Costa and colleagues showed that the number of newly recruited neurons decreased over 3 days of rotarod training, whereas the number of neurons no longer activated during the task increased. 14 Future studies using techniques to visualize individual neurons, such as activity-dependent protein expression (see, eg, Cao and colleagues 16 ) or miniscope imaging, 35 could help determine whether specific neuronal ensembles in the striatum are consolidated during rotarod learning.…”
Section: Striatal Activity During Rotarod Performancementioning
confidence: 99%
“…Optical in vivo imaging using cranial and spinal windows can be compared to imaging with miniaturized microscopes (miniscopes). In general, using the cranial and spinal window provides more expandability to combine with other techniques and a larger optical FOV [ 128 , 129 ]. Furthermore, multimodal imaging is easier for simultaneous acquisition of various data (neuronal activity, cerebral hemodynamics, structural imaging).…”
Section: Discussionmentioning
confidence: 99%